PERANAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN USAHA MASYARAKAT PADA DESA PESANGGRAHAN - Wilda Maulidina; M.Faisal Abdullah; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2019)
The purpose of this study was to determine the Role of Village-Owned Enterprises (BUM Desa) in enhancing Community-Based Enterprises (Case Study of Village-Owned Enterprises (BUM Desa) in Pesanggrahan Village, Batu City Batu District. This type of research is quantitative descriptive with different test methods. The results of this study show that BUM Desa Mayangsari, Desa Pesanggrahan has a role in increasing community businesses, in terms of granting capital loans. It is known from the increased business turnover, this is evidenced by a significant increase in turnover after and turnover before the role of BUM Desa Mayangsari (t arithmetic = 8,210, p value = 0,000) With the role of BUM Mayangsari Village, the community's operating income has increased, as evidenced by a significant increase in profit after and profit before the role of BUM Mayangsari Village (t arithmetic = 8.612 , p value = 0,000) With an increase in turnover and operating profit me show the role of Mayangsari Village-Owned Enterprises (BUM Desa) in increasing community businesses in Pesanggrahan Village.